Glutathione S-Transferase T1, O1 and O2 Polymorphisms Are Associated with Survival in Muscle Invasive Bladder Cancer Patients - Djukic, Tatjana I.; Savic-Radojevic, Ana R.; Pekmezovic, Tatjana D.; Matic, Marija G.; Pljesa-Ercegovac, Marija S.; Coric, Vesna M.; Radic, Tanja M.; Suvakov, Sonja R.; Krivic, Biljana N.; Dragicevic, Dejan P.; Simic, Tatjana P. (PloS one, 2013)
To examine the association of six glutathione transferase (GST) gene polymorphisms (GSTT1, GSTP1/rs1695, GSTO1/rs4925, GSTO2/rs156697, GSTM1, GSTA1/rs3957357) with the survival of patients with muscle invasive bladder cancer and the genotype modifying effect on chemotherapy. A total of 105 patients with muscle invasive bladder cancer were included in the study. The follow-up lasted 5 years. The effect of GSTs polymorphisms on predicting mortality was analyzed by the Cox proportional hazard models, while Kaplan-Meier analysis was performed to assess differences in survival. GSTT1 active, GSTO1 Asp140Asp or GSTO2 Asp142Asp genotypes were independent predictors of a higher risk of death among bladder cancer patients (HR = 2.5, P = 0.028; HR = 2.9, P = 0.022; HR = 3.9, P = 0.001; respectively) and significantly influenced the overall survival. There was no association between GSTP1, GSTM1 and GSTA1 gene variants with overall mortality. Only GSTO2 polymorphism showed a significant effect on the survival in the subgroup of patients who received chemotherapy (P = 0.006). GSTT1 active genotype and GSTO1 Asp140Asp and GSTO2 Asp142Asp genotypes may have a prognostic/pharmacogenomic role in patients with muscle invasive bladder cancer.